Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/adfm.201602262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Optically Complex, Porous, and Anisometric Polymeric Microparticles by Templating from Liquid Crystalline Droplets

Abstract: It is demonstrated that aqueous dispersions of micrometer-sized liquid crystal (LC) droplets provide the basis of a general and facile methodology for the templated synthesis of spherical and nonspherical polymeric microparticles with complex internal structure and porosity. Specifi cally, nematic droplets of reactive (RM257)/nonreactive mesogens with distinct internal confi gurations are prepared using a range of approaches, the reactive mesogens are photopolymerized, and then the nonreactive mesogens are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 77 publications
6
69
0
Order By: Relevance
“…The shrinkage perpendicular to the nematic director was linearly dependent on the reactive mesogen content whereas it was almost independent of the reactive mesogen content along the nematic director similar to the previous studies . This difference in the shrinkage of the microparticles along and perpendicular to the nematic director resulted in a linear concentration dependency of the aspect ratio of the microparticles maintained after the extraction of the unreacted mesogens, consistent with the past studies on the LC emulsion polymerization . However, the extent of the shrinkage we observed in this study was slightly higher than that observed in past studies .…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The shrinkage perpendicular to the nematic director was linearly dependent on the reactive mesogen content whereas it was almost independent of the reactive mesogen content along the nematic director similar to the previous studies . This difference in the shrinkage of the microparticles along and perpendicular to the nematic director resulted in a linear concentration dependency of the aspect ratio of the microparticles maintained after the extraction of the unreacted mesogens, consistent with the past studies on the LC emulsion polymerization . However, the extent of the shrinkage we observed in this study was slightly higher than that observed in past studies .…”
Section: Methodssupporting
confidence: 90%
“…Figure C shows the shrinkage percentage of the microparticles along and perpendicular to the nematic director as a function of the reactive mesogen content. The shrinkage perpendicular to the nematic director was linearly dependent on the reactive mesogen content whereas it was almost independent of the reactive mesogen content along the nematic director similar to the previous studies . This difference in the shrinkage of the microparticles along and perpendicular to the nematic director resulted in a linear concentration dependency of the aspect ratio of the microparticles maintained after the extraction of the unreacted mesogens, consistent with the past studies on the LC emulsion polymerization .…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Firstly, the phase difference parameter Φ introduced in was calculated: Φ(θ( z )) = ΔΦ(θ( z ))/ΔΦ max (θ 0 ), where ΔΦ is the phase retardation difference and θ( z ) is the LC director distribution. ΔΦ(θ( z )) is described by the formula as follows: normalΦ=2πλ[]L2+L2noneitalicdz()no2cos2θ()z+ne2sin2θ()z12noL. …”
Section: Simulation Resultsmentioning
confidence: 99%
“…There are porous systems made of polymers or solid crystals with the LC incorporated into the pores or confined space: polymer dispersed liquid crystals (PDLC), polymer stabilzed liquid crystals, fibers, porous silicon, or porous anodized aluminum oxide . Recently, many developments are described with mesogens comprising microparticles and nanoparticles for reduction of operation voltage or switching time . Such particles can have different shape: almost spherical, elongated like nanowires or disc‐like.…”
Section: Introductionmentioning
confidence: 99%